Pengaruh Arus Modal Asing dan Perbedaan Suku Bunga Global terhadap Stabilitas Sistem Keuangan - Oktafianto, Hasbi Dwi; Ar Rachman, Hajar Chair; Maulana, Rizal; Perwito, Perwito (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The purpose of the study is to test and analyze the Influence of Foreign Capital Flows and Global Interest Rate Differences on the Stability of the Financial System of Developed and Developing Countries in the period 2014 - 2024 both partially and simultaneously. This type of research uses a quantitative approach, namely, the sampling technique using purposive sampling. Data analysis used was panel data regression analysis. Statistical test using Software Eviews 12. The samples obtained were 3 with observation results of 33 samples. The results of the analysis show that the NCI has not had a significant effect on the stability of the financial system, indicating that the volatility of international capital flows does not directly weaken banking resilience. Conversely, TEAL has a positive and significant effect on financial system stability, signaling that well-managed global financial integration can strengthen banking resilience through risk diversification and access to international liquidity. Simultaneously, NCI and TEAL have a significant effect on the stability of the financial system with a very high level of clear power of the model. These findings underscore the importance of the role of financial intermediaries in managing global risks and strengthening financial system stability amid increasing international financial integration.